Penilaian Lanskap untuk Pembangunan Berkelanjutan: Studi Kasus di Perumahan Alam Sutera - Seanders, Olivia; Yuslim, Silia; Fitri, Rini (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2025)
Gated community-based housing development has become the leading choice in big cities in Indonesia, including Alam Sutera Housing South Tangerang. Despite offering comfort and security, sustainable landscape management remains a significant challenge, especially in relation to managing natural resources and the environment. This research aims to assess the landscape's character by considering ecological, social, and environmental sustainability aspects, as well as its impact on residents' quality of life. This research uses a quantitative descriptive approach, collecting data through questionnaires, field observations, and descriptive data analysis. The research results show that improvements in local crop management, green energy, and water management are needed to support sustainability. This research recommends increased use of local plants, more functional green open space design, and more efficient management of natural resources to support residents' quality of life and sustainability goals.